Strong antimicrobial activity of xanthohumol and other derivatives from hops (Humulus lupulus L.) on gut anaerobic bacteria - Cermak, Pavel; Olsovska, Jana; Mikyska, Alexandr; Dusek, Martin; Kadleckova, Zuzana; Vanicek, Jiri; Nyc, Otakar; Sigler, Karel; Bostikova, Vanda; Bostik, Pavel (APMIS, 2017)
Anaerobic bacteria, such as Bacteroides fragilis or Clostridium perfringens, are part of indigenous human flora. However, Clostridium difficile represents also an important causative agent of nosocomial infectious antibiotic-associated diarrhoea. Treatment of C. difficile infection is problematic, making it imperative to search for new compounds with antimicrobial properties. Hops (Humulus lupulus L.) contain substances with antibacterial properties. We tested antimicrobial activity of purified hop constituents humulone, lupulone and xanthohumol against anaerobic bacteria. The antimicrobial activity was established against B. fragilis, C. perfringens and C. difficile strains according to standard testing protocols (CLSI, EUCAST), and the minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBC) were calculated. All C. difficile strains were toxigenic and clinically relevant, as they were isolated from patients with diarrhoea. Strongest antimicrobial effects were observed with xanthohumol showing MIC and MBC values of 15-107 μg/mL, which are close to those of conventional antibiotics in the strains of bacteria with increased resistance. Slightly higher MIC and MBC values were obtained with lupulone followed by higher values of humulone. Our study, thus, shows a potential of purified hop compounds, especially xanthohumol, as alternatives for treatment of infections caused by select anaerobic bacteria, namely nosocomial diarrhoea caused by resistant strains.
Keywords: flavonoidy; Microbial Sensitivity Tests; průjem; Flavonoids; Plant Extracts; anaerobióza; Anaerobiosis; terpeny; Humans; anaerobic bacteria; Humulus; Diarrhea; mikrobiální testy citlivosti; lidé; symbióza; antibakteriální látky; rostlinné extrakty; propiofenony; Terpenes; Propiophenones; Clostridium; Symbiosis; infekce spojené se zdravotní péčí; Bacteroides fragilis; Clostridioides difficile; pseudomembranózní enterokolitida; Anti-Bacterial Agents; gut; Clostridium perfringens; Enterocolitis, Pseudomembranous; Cyclohexenes; Xanthohumol; cyklohexeny; Cross Infection